A Fast and Inexpensive Protocol for Empirical Verification of Neutralizing Epitopes in Microbial Toxins and Enzymes - Vuong, Christine N.; Chou, Wen-Ko; Kuttappan, Vivek A.; Hargis, Billy M.; Bielke, Lisa R.; Berghman, Luc R. (Frontiers in Veterinary Science, 2017)
In vivo targeting of peptides to antigen-presenting cells by use of agonistic anti-CD40 monoclonal antibodies has been used successfully as an immune response enhancing strategy. When tested in chickens, the antibody-guided platform was capable of inducing specific IgG production within one week post-immunization. However, use of this method beyond its initial conception as a vaccine delivery tool has not been fully exploited. In this study, Clostridium perfringens alpha-toxin was used as a model microbial toxin for epitope mapping by using the antibody-guided immunization method to generate a panel of antibodies against specific regions of the toxin in an attempt to identify crucial determinants on the toxin, which once bound, would hinder downstream toxicity. Alpha-toxin, which possesses both hemolytic and phospholipase C enzymatic activities, has long been known to be one of the key destructive etiological agents of necrotic enteritis disease in poultry. Previous attempts to identify crucial antigenic determinants on the toxin mediating its enzymatic activities have been performed using expensive and labor-intensive site-directed mutagenesis techniques. To create a panel of antibodies, twenty-three short candidate alpha-toxin peptide regions were selected in silico using B-cell epitope prediction algorithms in the public domain and were custom synthesized to load onto the antibody-guided complex for immunization in birds for antisera production. Peptide-specific antibody responses were generated against all candidate neutralizing epitopes and used for in vitro toxin neutralization tests. Antisera against all 23 peptides were able to neutralize the toxin’s hemolytic activity, with neutralization titers ranging from 80 to 320, but none were effective in blocking phospholipase C. The novel approach of antibody-guided immunization introduces a new, inexpensive method for polyclonal IgG production and de facto identification of neutralizing epitopes in microbial toxins and enzymes within two weeks from in silico analysis of a putative target sequence.